Hydrogen Peroxide: Its Role in Plant Biology and Crosstalk with Signalling Networks - Černý, Martin; Habánová, Hana; Berka, Miroslav; Luklová, Markéta; Brzobohatý, Břetislav (International journal of molecular sciences, 2018)
Hydrogen peroxide (H₂O₂) is steadily gaining more attention in the field of molecular biology research. It is a major REDOX (reduction⁻oxidation reaction) metabolite and at high concentrations induces oxidative damage to biomolecules, which can culminate in cell death. However, at concentrations in the low nanomolar range, H₂O₂ acts as a signalling molecule and in many aspects, resembles phytohormones. Though its signalling network in plants is much less well characterized than are those of its counterparts in yeast or mammals, accumulating evidence indicates that the role of H₂O₂-mediated signalling in plant cells is possibly even more indispensable. In this review, we summarize hydrogen peroxide metabolism in plants, the sources and sinks of this compound and its transport via peroxiporins. We outline H₂O₂ perception, its direct and indirect effects and known targets in the transcriptional machinery. We focus on the role of H₂O₂ in plant growth and development and discuss the crosstalk between it and phytohormones. In addition to a literature review, we performed a meta-analysis of available transcriptomics data which provided further evidence for crosstalk between H₂O₂ and light, nutrient signalling, temperature stress, drought stress and hormonal pathways.
Keywords: rostliny; biologický transport; signální transdukce; Gene Expression Regulation, Plant; Plant Development; transkriptom; plant hormone; Biological Transport; Stress, Physiological; H2O2; Signal Transduction; vývoj rostlin; stress; peroxid vodíku; regulátory růstu rostlin; fyziologický stres; Transcriptome; Plants; growth and development; regulace genové exprese u rostlin; Plant Growth Regulators; Hydrogen Peroxide; signalling